PERCOBAAN TINDAK PIDANA (POGGING) - Dany Try Hutama Hutabarat; Rika Aufara; Erwina Rosita; Muliati Hasibuan; Muhammad Reza Marpaung; Muhammad Afrizal Yuda; Herman Herman; Dini Anggraini; Rahmaniah Rahmaniah; Ibnu Tawaf; Shamil Basayef; Yusril Chandra; Fakhrul Azmi; Robby Ramadani; Arief Wardana (Nusantara Hasana Berdikari, 2022)
Experiment has the meaning of trying to do something evil, but the result does not happen not on the basis of his own will. The problem of being able and incapable of trial arises in connection with the execution of the act, but the intended offense is not completed or the result which is prohibited by law does not arise. In the case of an attempted crime, according to Article 53 paragraph (2) of the Criminal Code, the maximum penalty that can be imposed is the maximum penalty for a crime in accordance with the article in question, then reduced by one third.